Strengthening the Criminal Law System for National Defense Against Automated Cyber Attacks Based on “Artificial Intelligence” - Adriani Maylinda Christina Linda (Westscience Press, 2026)
The development of artificial intelligence (AI) has given rise to automated cyberattacks such as botnets, deepfakes, and adaptive DDoS attacks that challenge the Indonesian criminal justice system due to the complexity of perpetrator identification, legal evidence, digital anonymity, and regulatory gaps in the ITE Law No. 11/2008 and the PDP Law No. 27/2022. This multidisciplinary legal normative research analyzes these challenges through expert interviews, TensorFlow simulations, and a comparison of Indonesia, Japan, and the Netherlands, resulting in the innovative concept of the